The Role of Clinical Instructors in Guiding Nursing Students during Clinical Practice at Gunung Maria Hospital - Toreh, Pricilia Maria; Ria, Maria Novita (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Nursing education requires the integration of theory and practice; therefore, clinical mentoring plays an essential role in shaping students’ competencies. Clinical Instructors serve as educators, caregivers, and role models who directly influence the success of clinical learning. This study aims to identify and analyze the role of Clinical Instructors in implementing clinical mentoring for students at Gunung Maria Hospital, Tomohon. The study employed an analytical observational design with a cross-sectional approach, involving all Clinical Instructors who met the inclusion criteria through a total sampling technique. The instrument used was a questionnaire that had been tested for validity and reliability prior to administration. Data were analyzed univariately using frequency distributions. The results indicated that the majority of respondents rated the role of Clinical Instructors as good (70%), while 24% rated it as adequate and 6% as poor. Strong performance was particularly evident in educational roles, motivational support, and professional role-modeling for students. However, several limitations were identified, including limited interaction intensity, inconsistent feedback, and restricted mentoring time due to workload demands. In conclusion, the role of Clinical Instructors has generally been implemented effectively and contributes positively to the development of nursing students’ competencies, although improvements are still needed in consistency and mentoring strategies. The study recommends continuous training for Clinical Instructors on effective clinical mentoring approaches, institutional policies to optimize the instructor–student ratio, and strengthened collaboration between hospitals and educational institutions to enhance the overall quality of clinical learning.